Recommendations on the management of multiple myeloma in 2020. Issue 2 (4th March 2022) - Vekemans, Marie-Christiane; Doyen, Chantal; Caers, Jo; Wu, Kalung; Kentos, Alain; Mineur, Philippe; Michaux, Lucienne; Delforge, Michel; Meuleman, Nathalie
ABSTRACT: With the introduction of immunomodulatory drugs, proteasome inhibitors, and anti-CD38 monoclonal antibodies, major improvements have been achieved in the treatment of multiple myeloma (MM), with a significant impact on the outcome of this disease. Different treatment combinations are now in use and other therapies are being developed. Based on an extensive review of the recent literature, we propose practical recommendations on myeloma management, to be used by hematologists as a reference for daily practice.